Achievement motive and sport participation. (November 2016) - Gröpel, Peter; Wegner, Mirko; Schüler, Julia
Abstract: Three studies investigated the relationship between the achievement motive and sport participation. It was expected that both the implicit and the explicit achievement motives are positively associated with how frequently people engage in sport activities. The implicit achievement motive was assessed with indirect motive measures; the explicit achievement motive was either inferred from participants' personal goals or measured with self-reports. Two hundred five athletes participated including college students enrolled in leisure sport programs offered at their university (Study 1), amateur athletes registered in sports clubs (Study 2), and elite tennis athletes (Study 3). The implicit achievement motive consistently predicted sport participation in all three studies. In contrast, the explicit achievement motive was uncorrelated with sport participation. The interaction between the two motives did not yield an effect on sport participation. The results indicate that the implicit, unconscious need to achieve facilitates regular engagement in sport activities, but the explicit, conscious orientation toward achievement does not. The enrichment of sports environments with incentives for the implicit achievement motive may thus attract more people to participate in sport activities. Highlights: The implicit achievement motive predicts sport participation. The explicit achievement motive is uncorrelated with sport participation. Athletes' implicit and explicit affiliation motives are not correlated.